The effect of gelatinized brown rice extract on type 2 diabetes mellitus via inhibition of insulin resistance mediators in HepG2 cells - Min Ho Kang; Ha Young Park; Yeop Jang; Jung Eun Park; Jin Woo Kim (Discover Food)
Abstract The purpose of this study evaluated effects of gelatinized brown rice extract (GBE) on type 2 diabetes mellitus by analyzing antioxidant activity, polysaccharide-degrading enzymes activity, and regulation of insulin secretion and glucose transport-related factors in human liver cells (HepG2). Quantified polyphenols and flavonoids in extract showed 6.7 mg gallic acid equivalent/g dry matter (DM) and 5.3 mg quercetin equivalent/g DM, respectively, with DPPH and ABTS radical scavenging activities confirmed to 67.1 ~ 77.7%. Additionally, extract inhibited alpha-glucosidase activity by 81.9%, thereby demonstrating potential for improving blood glucose regulation. To demonstrate alleviation of type 2 diabetes through mitigation of insulin resistance and promotion of glucose transport, expression of genes related to insulin receptor genes (Insulin Receptor Substrate-1, Protein Kinase B) increased by 18.5 ~ 28.3%, while expression of counterregulatory hormone genes (Insulin-like Growth Factor-1) decreased by 33.3%. Additionally, expression of glucose transporter proteins (Glucose Transporter Type-4, 2) increased by 30.9 ~ 42.0%, and expression of proteins that reduce insulin sensitivity (Insulin Receptor Substrate-2) decreased by 34.6%. These results indicated that insulin resistance in hepatocytes alleviated, and glucose transport promoted, leading to decreased blood glucose levels.